A method to produce high contrast vein visualization in active dynamic thermography (ADT) - Saxena, Ashish (2022)
In this study, a method that will aid in the visualization of vein topology on a target area on the body of a human subject is demonstrated. An external cooling means is configured to cool the left forearm of fourteen study participants, effecting an active thermal change or recovery in the target area upon removal of cooling. An infrared (IR) thermal camera was used to capture a series of transient thermal images. These images were then processed to extract Dynamic synthetic images (SI) throughout the active thermal change or recovery process. Dynamic SI was calculated using a quantitative parameter called tissue activity ratio (TAR), which is defined by the rate of rewarming to the rate of cooling at each pixel of interest. A fixed step size of rewarming temperature (0.5 °C) was used to progressively extract multiple synthetic images throughout the whole recovery process. Compared to a Static SI extraction method, where only a single SI results from the whole active dynamic thermography (ADT) sequence, this study demonstrates a live feed of high contrast vein visualizations by using the Dynamic SI method. Furthermore, the dependency of Dynamic SI contrast on the temperature of the external cooling stimulation was investigated. Three cooling stimulation temperatures (5 °C, 8 °C, and 11 °C) were tested, where no statistically significant difference in the resulting SI contrast was found. Lastly, a discussion is put forth on assisting venipuncture or cannulation-based clinical applications, through the incorporation of the proposed method with a projection system.